2000
DOI: 10.1159/000010285
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Sonohysterography for the Evaluation and Treatment of Retained Products of Conception

Abstract: Diagnosing retained products of conception in a woman presenting with postpartum or postabortion bleeding presents a clinical challenge. Although ultrasonographic examination may be potentially useful in detecting retained products of conception, its accuracy has not yet been established. Saline infusion sonohysterography is a simple ultrasonographic technique for enhanced transvaginal sonographic imaging of the endometrial cavity by the instillation of saline into the uterine cavity during ultrasonographic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Although sonohysterography alone was previously shown to have high specificity and sensitivity for the detection of residual trophoblastic tissue, 5,16 the demonstration by color Doppler imaging of blood flow in the intrauterine solid masses had a 100% specificity for the diagnosis of residual trophoblastic tissue. Tal et al 6 also found that the use of color Doppler imaging during sonohysterography significantly increased the diagnostic accuracy in 4 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although sonohysterography alone was previously shown to have high specificity and sensitivity for the detection of residual trophoblastic tissue, 5,16 the demonstration by color Doppler imaging of blood flow in the intrauterine solid masses had a 100% specificity for the diagnosis of residual trophoblastic tissue. Tal et al 6 also found that the use of color Doppler imaging during sonohysterography significantly increased the diagnostic accuracy in 4 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonographic examination may be potentially useful, its accuracy has not yet been established. Saline infusion sonohysterography has enhanced our ability to diagnose retained products of conception (126). Alcazar (127) tried transvaginal B-mode ultrasonography combined with color velocity imaging and pulsed Doppler to detect retained trophoblastic tissue and concluded that this investigation could be useful to detect retained trophoblastic tissue and to select patients suitable for conservative management.…”
Section: Prevention Of Asherman Syndromementioning
confidence: 99%
“…Retained products of conception (RPOC) occurs following parturition or termination of pregnancy in nearly 1 percent of all pregnancies [1]. The incidence of RPOC is the highest after termination of pregnancy and second-trimester deliveries [2].…”
mentioning
confidence: 99%